ANALISIS PENERAPAN ETIKA BISNIS PADA PERUSAHAAN WARALABA DI LABBAIK CHICKEN CABANG KAMPUNG BALI KOTA BENGKULU - Milla, Hilyati; Suryani, Ade Irma; Sawaludin, Muhammad Rustu (Jurnal Pendidikan dan Ekonomi (JUPEK), 2025)
This study analyzes the application of business ethics at the Labbaik Chicken franchise company, Kampung Bali Branch, Bengkulu City. The rapidly growing franchise concept demands ethical consistency in its operations, especially in the fast food sector that is in direct contact with consumers. The purpose of this study is to describe and analyze how the principles of business ethics, especially the aspects of honesty, transparency, responsibility, and fairness, are applied in daily service practices. Using a descriptive qualitative approach, data were collected through in-depth interviews with supervisors, employees, and customers, as well as participant observation and documentation studies of the company's SOP. Data analysis was carried out using the Miles and Huberman interactive model. The results of the study indicate that Labbaik Chicken, Kampung Bali Branch has attempted to implement business ethics through SOPs and employee awareness. However, inconsistencies were found in the delivery of less transparent promotional information and a complaint handling mechanism that was not yet systematic. The implications of this study highlight the importance of internalizing ethical values ​​and increasing consistency in service to maintain customer trust and the image of the franchise company.